2023
DOI: 10.3389/fimmu.2023.1125634
|View full text |Cite
|
Sign up to set email alerts
|

The role of indoleamine 2,3-dioxygenase 1 in early-onset post-stroke depression

Abstract: BackgroundThe immune-inflammatory response has been widely considered to be involved in the pathogenesis of post-stroke depression (PSD), but there is ambiguity about the mechanism underlying such association.MethodsAccording to Diagnostic and Statistical Manual of Mental Disorders (5th edition), depressive symptoms were assessed at 2 weeks after stroke onset. 15 single nucleotide polymorphisms (SNPs) in genes of indoleamine 2,3-dioxygenase (IDO, including IDO1 and IDO2) and its inducers (including pro-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…[ 39 ] Moreover, it can upregulate the expression of indolamine 2,3-dioxygenase (IDO enzyme), increase the metabolic consumption of tryptophan, the precursor of 5-HT, and then reduce the synthesis of 5-HT, leading to the occurrence of depression. [ 40 , 41 ] The results of this study suggested that the mechanism of Baduanjin exercise combined with REBT to improve mood and sleep disorders in PSD patients is related to the increase of serum 5-HT and BDNF levels and the decrease of IL-6 levels. In addition, this study found that the MBI scores (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…[ 39 ] Moreover, it can upregulate the expression of indolamine 2,3-dioxygenase (IDO enzyme), increase the metabolic consumption of tryptophan, the precursor of 5-HT, and then reduce the synthesis of 5-HT, leading to the occurrence of depression. [ 40 , 41 ] The results of this study suggested that the mechanism of Baduanjin exercise combined with REBT to improve mood and sleep disorders in PSD patients is related to the increase of serum 5-HT and BDNF levels and the decrease of IL-6 levels. In addition, this study found that the MBI scores (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…PSD is diagnosed and defined by the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria. A person must present at least five out of following nine symptoms: feelings of guilt, a sad mood, decreased energy levels, insomnia, decreased appetite, decreased concentration, changes in psychomotor activity (decreased or increased), and recurrent thoughts of selfharm or suicide and loss of interest in pleasurable activities (anhedonia) that lasts for at least 2 weeks [15]. Nevertheless, DSM-5 is not used for some exceptional cases when diagnosing patients do not exhibit typical psychological symptoms and cannot describe their psychological conditions coherently [16].…”
Section: The Definition and Diagnosis Of Psdmentioning
confidence: 99%
“…PSD occurs at any time point following stroke. A clinical study about 186 acute stroke patients in hospitals have reported that 31.72% of these patients were identified as suffering from depression within 2 weeks after stroke onset [15]. Mitchell et al have reported in their comprehensive meta-analysis that one-third stroke patients had depressive disorders after a stroke [20].…”
Section: The Frequency Of Psdmentioning
confidence: 99%
“…Pro-inflammatory cytokines can accelerate Trp metabolism through the activation of IDO, reducing 5-HT synthesis and increasing neurotoxic quinolinic acid (QA) production, thus contributing to PSD [120]. Interestingly, the absence of IDO gene abnormalities prevents depression the onset of even under inflammatory stimuli [121](Shown in Fig. 3).…”
Section: 4mentioning
confidence: 99%